White Ferocity : The Genocides of Non-Whites and Non-Aryans from 1492 to Date - Plumelle-Uribe, Rosa Amelia (Codesria book series., 2020)
The slave trade, the conquest of the Americas and the invasion of Africa have deeply transformed the relations between Europeans and other groups. The jump from difference to superiority and racial hierarchy was so swift that it led to the moral collapse of Europe and North America. By shifting the devaluation of so-called 'inferior' beings from non-Whites to non-Aryans, Nazism committed the unforgivable crime of bringing into the heart of the European world a ferocity up to then reserved for other continents. In this book, White Ferocity: The Genocides of Non-Whites and Non-Aryans from 1492 to Date, Plumelle-Uribe investigates and demonstrates, with harrowing evidence and analyses, how Europeans justified the destruction of other peoples as unavoidable based on the officially declared belief of others being inferior.